IMPROVING BASIC ENGLISH SKILL OF POLBENG FIRST SEMESTER STUDENTS BY USING WEB-BASED LEARNING MATERIALS - Ari Satria; Arita Destianingsih; Safra Apriani Zahraa (INOVISH JOURNAL, 2018)
Abstract: The aims of this study was to describe the learning atmosphere when the implementation of Web-based learning materials and to find out how the improvement of the students’ basic skill during the implementation of Web-based learning materials. This was classroom action research type of research. The participants of this research were the Business Administration students of State Polytechnic Bengkalis. This research was conducted in two cycles by following the procedure of action research, i.e. planning, implementing, observing, and reflecting. In collecting the data, the researcher used observation, interview, questionnaire, and test. The data were analyzed qualitatively and quantitatively. The qualitative data were analyzed using Interactive Model of Data Analysis as propounded by Matthew M. Miles and A.M. Huberman. The results of the research showed that the learning atmosphere also improved. The class became more active, confident, and enjoyable. Furthermore, a Web-based learning material was able to improve the students’ Basic English Skill. It was proven by the increase of the students’ mean score from 41.22 in pre-test to 46.74 in cycle 1, and 49.92 in cycle 2. This result shows that the use of Web-based learning materials has proven to be an effective way in teaching-learning of Basic English skill.